Alexander Georg Supan - v Sloveniji spregledan geograf slovenskega rodu - Cigale, Dejan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2016)
Paper presents life and work of Alexander Supan, geographer of Slovenian origin, and his influence on global and Slovenian geography. He was one of the more important geographers of the second half of the 19th and at the beginning of the 20th century. His scientific work took place, in contrast to geographers who were then working in present-day Slovenian territory, in accordance with contemporary geographic approaches. He built his career abroad, but he started it in Ljubljana. Because of that and because of his origin, we can consider him one of the more important links in the history of modern geography in Slovenian territory.
Keywords: biografije; geografija; geography; slovenski geografi; Supan, Alexander Georg, 1847-1920; zgodovinski pregledi